Spatiotemporal patterns of vegetation conversion under the Grain for Green Program in southwest China. Issue 2 (6th December 2021) - Zhao, Haiwei; Wu, Ruidong; Yang, Feiling; Hu, Jinming; Wang, Junjun; Guo, Yang; Feng, Zhixue; Zhang, Chen; Wang, Yiting; Zhou, Jian
Abstract: China's Grain for Green Program (GGP) is the largest reforestation program in the world. Previous studies lacked targeted assessments regarding its effectiveness in vegetation conversion. Using the time series of Vegetation Continuous Fields in southwest China, we derived the spatiotemporal variations in total vegetation cover, short vegetation (SV) cover and tree canopy (TC) cover during the period from 2000 to 2016. By conducting residual trend analyses independently on the SV and TC cover time series, the trends in human‐induced SV cover (SVH ) and TC cover (TCH ) were detected. Then, we performed overlay analyses to derive the human‐induced SV–TC conversion in cropland. The study found that the SV in southwest China showed a net browning trend whereas the TC presented a net greening trend. Approximately 69.5% of the pixels with a significant browning trend in SVH showed a significant greening trend in TCH . Furthermore, 50.6% of the human‐induced SV–TC conversion in southwest China occurred in cropland, and the proportion was even larger for the eastern provinces. Our study provides a targeted evaluation of the performance of the GGP and highlights that the implementation of the GGP has caused widespread SV–TC conversion that potentially mitigates global climate change. Abstract : The Grain for Green Program has caused extensive vegetation conversion from short vegetation to forest in southwest China. Approximately 50.6% of human‐induced vegetation conversion occurred in cropland under the Grain for Green Program. The vegetation greening trend in southwest China was primarily contributed by forest gain.